Sociocultural narratives and the anthropomorphic power of agency in a semiotic landscape. Issue 2 (3rd April 2021) - Simungala, Gabriel; Jimaima, Hambaba
Abstract: We take the conflation of space, time and the sociopolitical ideology in the newly independent Zambia as a transformative semiotic capacity predicated on notions of resemiotisation and metamorphosis of artefacts that are seen through the naming and names of hostels at the University of Zambia (UNZA). Borrowing from theories of semiotic assemblages and multilingual memory, the article seeks to show how Kaunda's United Independence Party and the government's ideologies permeated the linguistic landscape of the University of Zambia, in which the university becomes a copy of copies in order to engender a notion of home, school, nationhood and Pan-Africanism. By using names which represent the pride of Zambia, we show how Kaunda creatively emplaced on an institution a sense of nationhood which transcends ethnic enclaves and traditional affiliation and membership. We conclude by pointing out how, in hindsight, hostel names successfully reject fixity within a historical party ideological entrapment, and note rather, with the passage of time and admission of new actors to the space, the semiotic landscape of UNZA has continued to evolve to meet the current semiotic situation.